Immune features of the peritumoral stroma in pancreatic ductal adenocarcinoma - Ahmed, Azaz; Klotz, Rosa; Köhler, Sophia; Giese, Nathalia; Hackert, Thilo; Springfeld, Christoph; Jäger, Dirk; Halama, Niels (Frontiers in immunology, 2022)
Background: The peritumoral stroma is a hallmark of pancreatic ductal adenocarcinoma (PDA) with implications for disease development, progression and therapy resistance. We systematically investigated immune features of the stroma in PDA patients to identify markers of clinical importance and potential therapeutic targets. Methods: Tissue and blood samples of 51 PDA patients with clinical and follow-up information were included. Laser Capture Microdissection allowed us to analyze the stromal compartment in particular. Systematic immunohistochemistry, followed by software-based image analysis were conducted. Also, multiplex cytokine analyses (including 50 immune-related molecules) were performed. Functional analyses were performed using patient-derived 3D bioprints. Clinical information was used for survival analyses. Intercompartmental IL9 and IL18 gradients were assessed in matched samples of tumor epithelium, stroma, and serum of patients. Serum levels were compared to an age-matched healthy control group. Results: Stromal IL9 and IL18 are significantly associated with patient survival. While IL9 is a prognostic favorable marker (p=0.041), IL18 associates with poor patient outcomes (p=0.030). IL9 correlates with an anti-tumoral cytokine network which connects regulation of T helper (Th) 9, Th1 and Th17 cells (all: p<0.05 and r>0.5). IL18 correlates with a Th1-type cytokine phenotype and stromal CXCL12 expression (all: p<0.05 and r>0.5). Further, IL18 associates with a higher level of exhausted T cells. Inhibition of IL18 results in diminished Th1- and Th2-type cytokines. Patients with high stromal IL9 expression have a tumor-to-stroma IL9 gradient directed towards the stroma (p=0.019). Low IL18 expression associates with a tumor-to-stroma IL18 gradient away from the stroma (p=0.007). PDA patients showed higher serum levels of IL9 than healthy controls while serum IL18 levels were significantly lower than in healthy individuals. The stromal immune cell composition is distinct from the tumor epithelium. Stromal density of FoxP3+ regulatory T cells showed a tendency towards improved patient survival (p=0.071). Conclusion: An unexpected high expression of the cytokines IL9 and IL18 at different ends is of significance in the stroma of PDA and relates to opposing patient outcomes. Sub-compartmental cytokine analyses highlight the importance of a differentiated gradient assessment. The findings suggest stromal IL9 and/or IL18 as markers for patient stratification and as potential therapeutic targets. Future steps include investigating e. g. the role of local microbiota as both cytokines are also regulated by microbial compositions.
Gesehen am 20.01.2023